Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Bank BRI Syariah - Ruhul Amin; Siti Dina Hariroh (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The current era of globalization has an impact on the development of a business, organization or company consisting of many components that compose into one unit for the same purpose, motivation and discipline in working at BRI Syariah bank. This type of research is quantitative, using the method of observation, interviews, questionnaires and documentation. Multiple regression analysis tool. Based on the results of the study, it shows that there is a positive and significant effect between variable X1 on variable Y has a regression coefficient value of 2.762. There is a positive but not significant effect between variable X2 on variable Y has a regression coefficient value of -.223. There is a positive and significant effect simultaneously between variables X1 and X2 on variable Y. Variable X1 is a variable that is considered more dominant and significant to variable Y with a probability number of 0.016 and a regression coefficient value of 2.762.